أزمة وباء "كورونا" في الضفة الغربية المحتلة: بين الاستجابة الرسمية والتبعات الاقتصادية (قضايا سياسية, 2022)
This research discussed the most prominent economic effects of the Corona pandemic (Covid-19) in the West Bank, and the executive procedures taken by the Palestinian Authority to deal with this crisis, and its collision with the structural political and economic context in the occupied Palestinian environment related to the "Oslo Accords" and its outcomes, which contributed to deepening the effects and increasing obstacles, as well as the actions taken by the Palestinian government to address the effects and feasibility of the pandemic. The study is based on statistical indicators, press releases, official statements, and reports of international and private institutions.